Доступ до бази даних за допомогою entity framework - Фурманов, А. А. (ХНУРЕ, 2023)
This article provides an overview of the advantages and disadvantages of using Entity Framework (EF) [1] for database access. The benefits include increased development productivity, object-oriented programming, support for various database management systems, and the use of LINQ queries [2]. However, the drawbacks encompass performance limitations, increased memory consumption, complexity, and dependency on the database provider. Developers should carefully evaluate their project requirements, resources, and experience before choosing EF as their database technology